A Mini-Review: Possible Mechanisms of Hepatoprotective Effect of Aloe Vera Gel - Sri Handayani; Dina Aprilia; Khoirun Nisa; Vita Taufika Rosyida; Martha Purnami Wulanjati; Anjar Windarsih; Cici Darsih; Andri Frediansyah; Sari Haryanti (Indonesian Journal of Cancer Chemoprevention, 2021)
Protective agent for hepatotoxicity is still a great challenge in the management of liver diseases. Aloe vera is a beneficial plant that has been studied for food supplements, cosmetic and herbal medicine. Aloe vera contains many compounds which have a role in body health including polysaccharides, phenolic, flavonoid, terpenoid, amino acid, and several minerals. There have been compelling evidences that natural phytochemicals and their derivatives have hepatoprotective activities. Information of the aloe vera and its mechanism of action for possible hepatoprotective activities, including in silico, in vitro, and in vivo studies were obtained from Pubmed, Science Direct, Scopus, and Google scholar search engines. This current review was focusing on the possible contribution of compounds inside aloe vera gel and the suggestion of its mechanism on protective effect, especially for liver. The complexity of monosaccharides composition, backbone structures, acetyl group, and molecular weight of aloe polysaccharides have possible correlations with its hepatoprotective effect. Most of the hepatoprotective mechanisms of aloe compounds are related to their protective effect against inflammation and oxidative stress. Several compounds may have combination effects or several targets lead to synergistic effects.Keywords: Aloe vera, food supplement, hepatoprotective, liver disease, mechanism of action.